2007
DOI: 10.1016/j.jana.2007.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Stigma, Sexual Behaviors, and Abstinence Among Vietnamese Adolescents: Implications for Risk and Protective Behaviors for HIV, Sexually Transmitted Infections, and Unwanted Pregnancy

Abstract: As rates of HIV increase in Viet Nam, there is a need for data on social relations and sexual risk and protective behaviors among Vietnamese adolescents in a context of rapid social and economic changes. We report findings from our qualitative interviews with 159 Vietnamese adolescents living in Ha Noi, Nha Trang City and Ninh Hoa District and survey of 886 adolescents in these same three sites. In the qualitative interviews, youth report a strong adherence to ideals and values regarding abstinence outside of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 15 publications
5
50
0
Order By: Relevance
“…This has also been reported among young people from other countries (23,24), a finding that could be explained by intergenerational sexual relations in which female adolescents have sex with older male partners outside the studied age group (24). In Vietnam, stigma associated with premarital sex is seen as a significant hindrance to young women's abilities to negotiate and engage in safer sex (20). The non-condom use at sexual debut among females may also be because females are more likely to have first intercourse with a partner with whom they have intimate relationships (1), but this possibility was ruled out in the multivariate model.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This has also been reported among young people from other countries (23,24), a finding that could be explained by intergenerational sexual relations in which female adolescents have sex with older male partners outside the studied age group (24). In Vietnam, stigma associated with premarital sex is seen as a significant hindrance to young women's abilities to negotiate and engage in safer sex (20). The non-condom use at sexual debut among females may also be because females are more likely to have first intercourse with a partner with whom they have intimate relationships (1), but this possibility was ruled out in the multivariate model.…”
Section: Discussionsupporting
confidence: 76%
“…Similar to other East Asia countries, the low prevalence of safe sex behavior among adolescents and youths in their premarital period may stem from the pervasive social stigma against premarital sex. A qualitative study in Vietnam (20) suggested that this stigma could decrease young people's ability to prepare for the possibility of engaging in sexual behaviors. Despite awareness that condoms can prevent HIV and pregnancy, young people were not only reluctant to prepare for engaging in sex but also had limited social access to both information and condoms (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of premarital sex in Vietnam are reportedly low (Kaljee et al, 2007;Mensch, Clark, & Dang, 2002Zabin et al, 2009). For example, a 1999 survey of unmarried Vietnamese 15-to 22-year-olds in six provinces found that only 10% of boys and 5% of girls reported ever having had sex, lower than what was reported in some other Asian countries such as the Philippines and Thailand (Mensch et al, 2002(Mensch et al, , 2003.…”
Section: Background Premarital Sexual Practice In Contemporary Vietnammentioning
confidence: 95%
“…prospect for a good marriage and the damage of her social standing as well as that of her whole family (Go et al, 2002;Kaljee et al, 2007;Marr, 1997;Nhan & Hang, 1996;Pham, 1999).…”
Section: International Journal Of Sexual Healthmentioning
confidence: 99%